Strengthening National Identity Through The Learning of East Culture-Based Art Education (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2020)
Eastern culture-based art education is an effort to strengthen and build national identity through the transfer of knowledge and the transfer of value in the values of diversity and cultural preservation. The purpose of this study is to provide a conceptual picture of strengthening national identity through learning art education based on eastern culture. The method used is qualitative research by examining science theoretically through literature study, documentation, video, and audio study approaches that are analyzed descriptively. The results showed that some of the eastern cultural arts which are full of messages, moral values, and philosophy of life as a foundation for strengthening and building national identity through art education based on eastern culture are the arts of go laba, Ja’i, and reba traditional rituals. The art is a tradition of the people of Ngada, Flores, NTT which is used as an accompanying event in traditional rituals such as the ritual of making a new traditional house, the ritual of making customary symbols (ngadhu-bhaga), and the ritual of pesat kampung (ka nua). While, the conceptualization picture of strengthening the national identity through learning art education based on eastern culture can be done by; First, the stages of classification by selecting various kinds of art genres (music, dance, theater, visual) Eastern culture, to find meaning and values embodied in local wisdom. Second, the identification stage by identifying the learning of arts-based on eastern culture in the form of text and context into the realm of affective, cognitive, psychomotor, and creative. Third, the implementation stage by applying the results of classifying and identifying eastern culture-based art learning to be applied to students so they can understand the values contained in local culture and have cultural intelligence.